2005
DOI: 10.1016/j.precon.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette use among Greek athletes

Abstract: Background: Cigarette smoking is an important risk factor for cardiovascular disease and lung cancer. Exercise improves cardiovascular and pulmonary function and also may play an important role in encouraging people to give up smoking, when appropriate sporting activity is introduced. We investigated smoking habits among Greek students participating in sporting activities. Methods: We interviewed 1003 volunteers with a mean age of 17.9 ± 0.2 years. They included 617 (61.5%) men and 386 (38.5%) women, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The results of a study in Greece showed the highest numbers of male smokers were volleyball players, boxers and handball players whereas the highest rate of female smokers were volleyball players, dancers, gymnasts and basketball players [ 10 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study in Greece showed the highest numbers of male smokers were volleyball players, boxers and handball players whereas the highest rate of female smokers were volleyball players, dancers, gymnasts and basketball players [ 10 ] .…”
Section: Discussionmentioning
confidence: 99%
“…When the smoking habit of the elite sportsmen is analyzed, it was identified that the total of them were non-smokers (Table 2). When the other studies in this regard are analyzed, in Spanoudaki et al (2005)'s study on Greek athletes, the rate of the smoking habit among the athletes is 10.4 %. In Saygın et al (2009)'s study, the 25.4 % of the professional footballers are active smokers.…”
Section: Discussionmentioning
confidence: 99%